Endoplasmic reticulum stress and eIF2α phosphorylation: The Achilles heel of pancreatic β cells - Miriam Cnop; Sanna Toivonen; Mariana Igoillo-Esteve; Paraskevi Salpea (Elsevier, 2017)
Background: Pancreatic β cell dysfunction and death are central in the pathogenesis of most if not all forms of diabetes. Understanding the molecular mechanisms underlying β cell failure is important to develop β cell protective approaches. Scope of review: Here we review the role of endoplasmic reticulum stress and dysregulated endoplasmic reticulum stress signaling in β cell failure in monogenic and polygenic forms of diabetes. There is substantial evidence for the presence of endoplasmic reticulum stress in β cells in type 1 and type 2 diabetes. Direct evidence for the importance of this stress response is provided by an increasing number of monogenic forms of diabetes. In particular, mutations in the PERK branch of the unfolded protein response provide insight into its importance for human β cell function and survival. The knowledge gained from different rodent models is reviewed. More disease- and patient-relevant models, using human induced pluripotent stem cells differentiated into β cells, will further advance our understanding of pathogenic mechanisms. Finally, we review the therapeutic modulation of endoplasmic reticulum stress and signaling in β cells. Major conclusions: Pancreatic β cells are sensitive to excessive endoplasmic reticulum stress and dysregulated eIF2α phosphorylation, as indicated by transcriptome data, monogenic forms of diabetes and pharmacological studies. This should be taken into consideration when devising new therapeutic approaches for diabetes.